If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y + -1 = -3 Reorder the terms: -1 + y = -3 Solving -1 + y = -3 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + y = -3 + 1 Combine like terms: -1 + 1 = 0 0 + y = -3 + 1 y = -3 + 1 Combine like terms: -3 + 1 = -2 y = -2 Simplifying y = -2
| 0=49t+-9.8t | | 25+2x=-7(8x+4)+5x | | 6x-2=7x-8 | | 9p^2-9=891 | | -38=-4+2n | | 15-7x=x-6-5x | | Y-(8-y)=-20 | | 2a+3=-11 | | 15+8-12=x | | 12x+2=3x+11 | | 16x-18+6x+4=118 | | 32+8v=8(7v-2) | | -8=23-5q | | f(x)=5x^2-7x^3 | | -3-6x^2=-103 | | 1+6p=1-p | | 5+a=29 | | (11t-s)(t+5s)= | | -10x+2=-10 | | -10x+2=-11 | | -12=8+f2 | | 14000=36000-1500t | | 1400=36000-1500t | | -20=-5n+-3n | | 35=1-2a | | -41=2x-7 | | -5(6y-9)-y=-2(y-4) | | 4(x-3)=6(x+1) | | -2(5x-1)=11 | | n^2+5=105 | | -7x+24=8+x | | (2b-5)(2b+5)= |